Vocational education and training for sustainable development: : backgrounds, activities, initial results - Diettrich, Andreas [Verfasser]; Hahne, Klaus [Verfasser]; Winzier, Dagmar [Verfasser] (My University, 2009)
"Education for sustainable development has received something of a boost, this being evidenced by the UN Reports on Climate Development, by the declared will of politicians and political parties to strengthen climate protection and drive sustainability forwards and by the UN Decade of "Education for Sustainable Development" and its attendant national follow-up activities. The present paper explains the educational dimension of the central idea of "sustainable development" and describes the processes and findings which have emerged from the "Vocational Education and Training for Sustainable Development" programme (known by its German abbreviation of BBNE)." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; S 2.3 Berufsbildungspolitik; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Nachhaltige Entwicklung; Berufsbildung; Umweltbildung; Berufsbildungspolitik; Bundesinstitut für Berufsbildung